IMPLEMENTATION OF AGRIBUSINESS-BASED ISLAMIC BOARDING SCHOOL CURRICULUM - Sa’diyah, Maemunah; Ramdani, Ahmad; Lisnawati, Santi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2019)
Islamic boarding school as Islamic educational institution forms humans who have a high awareness of the agricultural environment. In Arabic vocabulary, the term curriculum is known as the manhaj which means the bright way or the bright path traveled by human in various fields of life. If this understanding is associated with education, then the manhaj or curriculum means a clear path taken by educators or teachers together with educated people (students) to develop their knowledge, skills and or attitudes. The purpose of life skills education is to make education work according to their nature, which is to develop the human potential of students to face their role in the future. Al-Musthafawiyah Islamic Boarding School is an educational institution which is quite successful in conducting plantation education while at the same time raising the economy of the community in Coblong village through its agribusiness activities. The research method used is descriptive qualitative. Al-Musthafawiyah Islamic boarding school was established separately from the community with the aim that the boarding school has space in forming the personalities of the students and does not mix with the culture of the surrounding community that is not in accordance with the objectives of establishing boarding schools. The education system at Al-Mushtafawiyah Islamic boarding school is to use an implementative, comprehensive and innovative curriculum so that students can and are increasingly developing to keep up with the times. At Al-Musthafafiyah Islamic Boarding School also conducts an integrated tarbiyah process which is: ruhiyah, aqliyah and jasadiyah and Al-Musthafawiyah Islamic Boarding School is an Islamic Boarding School that has a 24-hour parenting pattern and also an educational system used based on multimedia. The Agribusiness curriculum at Al-Musthafawiyah Islamic Boarding School has become a kind of companion, as well as the main activity of the curriculum. The main objective of this curriculum is to prepare the independence, skills and expertise that will be used by AlMusthafawiyah graduate students in the plantation sector.